Genetically Induced In Situ‐Poling for Piezo‐Active Biohybrid Nanowires. Issue 6 (13th December 2018) - Kilper, Stefan; Jahnke, Timotheus; Aulich, Marc; Burghard, Zaklina; Rothenstein, Dirk; Bill, Joachim
Abstract: Polycrystalline piezo‐active materials only exhibit a high macroscopic piezoresponse if they consist of particles with oriented crystal directions and aligned intrinsic dipole moments. For ferroelectric materials, the postsynthesis alignment of the dipoles is generally achieved by electric poling procedures. However, there are numerous technically interesting non‐ferroelectric piezo‐active materials like zinc oxide (ZnO). These materials demand the alignment of their intrinsic dipoles during the fabrication process. Therefore, in situ‐poling techniques have to be developed. This study utilizes genetically modified M13 phage templates for the generation of force fields, which directly control the ZnO dipole poling. By genetic modification of M13 phage template, the piezoelectric response of the ZnO/M13 phage hybrid nanowire is doubled compared to the hybrid nanowire based on unmodified M13 wild type (wt) phage templates. Thus, the formation of piezo‐active domains consisting of oriented ZnO nanocrystals is directly induced by the genetic modification. By the combination of the fiber‐like structure of individual M13 phages with the bioenhanced electromechanical properties of ZnO, hybrid nanowires with a length of ≈1.1 µm and a thickness of ≈63.5 nm are fabricated with a high piezoelectric coefficient of up to d 33 = 7.8 pm V −1 for genetically modified M13 phage templates. Abstract : Genetically modified M13 phage templates control the alignment of ZnO dipoles by dipole–dipole interactions. The formation of piezoactive domains consisting of oriented ZnO nanocrystals is directly induced by the genetic modification. Piezoelectric hybrid nanowires with a high piezoelectric coefficient of up to d 33 = 7.8 pm V −1 are fabricated.